2000
DOI: 10.1016/s0741-5214(00)90163-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative treatment with doxycycline reduces aortic wall expression and activation of matrix metalloproteinases in patients with abdominal aortic aneurysms

Abstract: In addition to its recognized effects as a direct MMP antagonist, Dox may influence connective tissue degradation within human aneurysm tissue by reducing monocyte/macrophage expression of MMP-9 mRNA and by suppressing the post-translational processing (activation) of proMMP-2. Through this complementary combination of mechanisms, treatment with Dox may be a particularly effective strategy for achieving MMP inhibition in patients with an AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
149
2
9

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(163 citation statements)
references
References 66 publications
3
149
2
9
Order By: Relevance
“…However it is not completely understood if the reduced number of metastases is due to a direct e ect of tetracyclines on MMP synthesis or on tumor cell proliferation. In this context studies on chemically modi®ed tetracycline type inhibitors on MMPs have shown that while MMPs can indeed be directly inhibited at the levels of transcription (Curci et al, 2000;Hanemaaijer et al, 1998) and function (Smith et al, 1999;Sorsa et al, 1998), many tumor and normal cell lines show a tetracycline-mediated growth inhibition which may be independent of the MMP blockade (Bettany and Wolowacz, 1998;Sledge, 1995, 1998;van den Bogert et al, 1985). This might explain the observation that doxycycline, administered at 20 mg/kg/day, signi®cantly inhibited tumor growth of mammary carcinoma cells subcutaneously injected in athymic mice (Fife and Sledge, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However it is not completely understood if the reduced number of metastases is due to a direct e ect of tetracyclines on MMP synthesis or on tumor cell proliferation. In this context studies on chemically modi®ed tetracycline type inhibitors on MMPs have shown that while MMPs can indeed be directly inhibited at the levels of transcription (Curci et al, 2000;Hanemaaijer et al, 1998) and function (Smith et al, 1999;Sorsa et al, 1998), many tumor and normal cell lines show a tetracycline-mediated growth inhibition which may be independent of the MMP blockade (Bettany and Wolowacz, 1998;Sledge, 1995, 1998;van den Bogert et al, 1985). This might explain the observation that doxycycline, administered at 20 mg/kg/day, signi®cantly inhibited tumor growth of mammary carcinoma cells subcutaneously injected in athymic mice (Fife and Sledge, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline belongs to the family of chemically modi®ed tetracyclines, which can suppress MMP activity in a variety of tissues and tumors (Sipos et al, 1994), as well as inhibit gelatinase activity in human breast carcinoma cells (Fife and Sledge, 1995). Although doxycycline has been considered a nonselective MMP inhibitor, published data suggest that this chemically modi®ed tetracycline seems to preferentially inhibit gelatinase B/MMP9 activity and expression in corneal epithelial (Sobrin et al, 2000) and human endothelial cells (Hanemaaijer et al, 1998), as well as reducing in vivo levels of MMP-9 in tissues from patients with thoracic aneurysms (Curci et al, 2000). These observations prompted us to analyse the e ect of doxycycline on MMP synthesis and consequent tumor vascularization in normal and a1-null mice.…”
Section: Introductionmentioning
confidence: 99%
“…15,24,27,36,91 MMP-9 inhibitors have showed utility in protection from ICH. [92][93][94] Inhibiting MMP-9 may also negate the harmful effects of AVMrelated inflammatory responses. Lee et al 28,29 evaluated the effect of the MMP-9 inhibitors minocycline and pyrrolidine dithiocarbamate on an AVM mouse model and showed that MMP-9 blockade significantly reduced the extent of hemorrhage.…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%
“…It has been documented that preoperative doxycycline treatment (for 7 days) in patients who underwent elective repair of an infrarenal AAA, reduced MMP-9 expression and post-translational processing of MMP-2 in aneurysmal tissues [76]. Interestingly, in a prospective phase II study (cohort n=36),…”
Section: Tetracyclinementioning
confidence: 98%